Boundaries of journalism professionalism, practices and participation - Carlson, Matt 1977-; Lewis, Seth C. (London Routledge, Taylor & Francis Group, 2015)
The concept of boundaries has become a central theme in the study of journalism. In recent years, the decline of legacy news organizations and the rise of new interactive media tools have thrust such questions as "what is journalism" and "who is a journalist" into the limelight. Struggles over journalism are often struggles over boundaries. These symbolic contests for control over definition also mark a material struggle over resources. In short: boundaries have consequences. Yet there is a lack of conceptual cohesiveness in what scholars mean by the term "boundaries" or in how we should think about specific boundaries of journalism. This book addresses boundaries head-on by bringing together a global array of authors asking similar questions about boundaries and journalism from a diverse range of perspectives, methodologies, and theoretical backgrounds. Boundaries of journalism assembles the most current research on this topic in one place, thus providing a touchstone for future research within communication, media and journalism studies on journalism and its boundaries.
Professionalism, norms and boundaries. Out of bounds: professional norms as boundary markers / Jane B. Singer -- Nothing but the truth: redrafting the journalistic boundary of verification / Alfred Hermida -- Divided we stand: blurred boundaries in Argentine journalism / Adriana Amado and Silvio Waisbord -- The wall becomes a curtain: revisiting journalism's news-advertising boundary / Mark Coddington -- Creating proper distance through networked infrastructure: examining google glass for evidence of moral, journalistic witnessing / Mike Ananny -- Hard news/soft news: the hierarchy of genres and the boundaries of the profession / Helle Sjøvaag -- Internal boundaries: the stratification of the journalistic collective / Jenny Wiik -- Encountering non-journalistic actors in newsmaking. Journalism beyond the boundaries: the collective construction of news narratives / David Domingo and Florence Le Cam -- Redrawing borders from within: commenting on news stories as boundary work / Sue Robinson -- Resisting epistemologies of user-generated content? cooptation, segregation and the boundaries of journalism / Karin Wahl-Jorgensen -- NGOs as journalistic entities: the possibilities, problems and limits of boundary crossing / Matthew Powers -- Drawing boundary lines between journalism and sociology, 1895-1999 / C.W. Anderson -- Epilogue.
Includes bibliographical references and index.
Keywords: Journalistic ethics; Journalism -- Objectivity